Qualitative and quantitative estimation of amino acids of the protein isolated from Marsh Mallow F. Part (1) - Basma Nafei Naemie (College of Education for Pure Sciences, 2013)
Abstract The research was concerned with Amino Acid Analysis of the proteins isolated from the crude aqueous extract of Marsh Mallow F. Acidic and Alkaline hydrolysis were performed. All amino acids had been appeared in Acidic hydrolysis, while in Alkaline hydrolysis for the same aqueous extract two amino acids serine and aspartic acid disappeared. The research also involved separation of the proteinous components from the aqueous extract of Marsh Mallow F. Two major proteins peaks (a and b) were isolated and their molecular weight were determined by gel filtration and showed the following values (281838, 281) dalton. respectively.